Biochemical changes in rats after treatment with soft drink and menthol flavoured candy - E. F. Isoje; I. O. Okoro; B. M. A. Ali; G. I. Edo; E. Yousif; J. Okpoghono; E. O. Okoro; S. U. Okom; A. E. A. Essaghah; H. Umar; J. O. Owheruo; P. O. Akpoghelie; et al. (Пищевые системы)
The current study looked at the biochemical variations that occurred in rats after they were given menthol flavoured candies and soft drinks. Seventy male Wistar albino rats in total were acquired, split up into ten treatments of seven rats each, and treated with the following regimen for forty-two days. Group 1 is the control. Groups 2, 3, and 4 received 8, 5, and 2.5 ml of La Casera/kg body weight. Groups 5, 6, and 7 received 0.34, 0.22, and 0.11 g of Tom-Tom/kg body weight. The dosages for groups 8, 9, and 10 were 8, 5, and 2.5 ml of La Casera/kg body weight, as well as 0.34, 0.22, and 0.11 g of Tom-Tom/kg body weight correspondingly. The results showed that the groups given Tom-Tom and La Casera had lower levels of total protein (TP) and albumin (Alb), and significantly (p < 0.05) higher serum levels of alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total cholesterol (T-Chol), triacylglycerol (TAG), and low-density lipoprotein cholesterol (LDL–C). Furthermore, there was a substantial (p < 0.05) increase in the serum levels of TP, Alb, and ALT between groups 7 and 5. Prolonged use of Tom-Tom mixed with La Casera should be avoided due to the detrimental alterations in biochemical parameters and subsequent health repercussions.